A luta das mulheres pela sobrevivência diária, na obra “O cortiço” de Aluísio de Azevedo comparada a luta no SÉCULO XXI - NATIVIDADE, Mayara Evangelista (2023)
Women's struggles have been present in our society since the last century, and these struggles continue to occur with great intensity today, we can see that although there are many changes daily, problems continue in the search for women's rights and equity. In this work, analogies were sought from the literary work O Cortiço, by Aluísio de Azevedo, from 1890, and the struggles of women in the 20th century, with the aim of comparing the struggles for survival of female characters in the work “O cortiço” with the struggles current women The development took place through bibliographical research in readings and analyzes based on authors who address the theme, based on the historical and social perspective present in the narrative of the literary work in question. The present work has great relevance for society, and especially for women, as it can serve as a means for them to realize how important the struggle of women is historically, in literature and how this is reflected in their lives today. From this analysis, it was possible to verify that the prejudices directed at women in the 19th century are still suffered today and the struggle for existence grows as society awakens, as female society fights for its rights and equality, and these women's movements, despite all the difficulties, provide social visibility and the conquest of rights, allowing a process of construction of more egalitarian social relations in terms of classes, color and gender.